2017
DOI: 10.12953/2177-6830/rcm.v8n3p142-150
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização do setor madeireiro de Rorainópolis, sul de Roraima

Abstract: RESUMO Buscou-se realizar um diagnóstico do setor madeireiro de Rorainópolis (Roraima) visando gerar informações que subsidiem o desenvolvimento de políticas públicas voltadas para a gestão florestal no Estado. Foi aplicado um questionário em nove serrarias com o intuito de obter informações sobre localização atual e anterior, tempo de atuação; espécie, volume de madeira serrada e origem da matéria prima; o destino da madeira processada; o tipo de armazenamento e de secagem. As serrarias eram empreendimentos n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
0
4
0
3
Order By: Relevance
“…An analysis of the horizontal structure in Ds showed that the three tree species with the greatest importance value (IV%) in descending order were Manilkara excelsa (11.7%), Qualea brevipedicellata (8.2%) and Goupia glabra (5.2%), exploited commercially in the region in the DL and PSFM categories (CONDÉ;TONINI, 2013;GIMENEZ et al, 2015;CRIVELLI et al, 2017). In LOt 1 , Manilkara huberi (Ducke) (35.2%), Qualea brevipedicellata (13.3%) and Dinizia excelsa (10.1%) had the highest IV values, while in LOt 2 , Manilkara excelsa (35.4%), Dinizia excelsa (10.7%) and Cordia glabrata (3.8%) had the highest IV values (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An analysis of the horizontal structure in Ds showed that the three tree species with the greatest importance value (IV%) in descending order were Manilkara excelsa (11.7%), Qualea brevipedicellata (8.2%) and Goupia glabra (5.2%), exploited commercially in the region in the DL and PSFM categories (CONDÉ;TONINI, 2013;GIMENEZ et al, 2015;CRIVELLI et al, 2017). In LOt 1 , Manilkara huberi (Ducke) (35.2%), Qualea brevipedicellata (13.3%) and Dinizia excelsa (10.1%) had the highest IV values, while in LOt 2 , Manilkara excelsa (35.4%), Dinizia excelsa (10.7%) and Cordia glabrata (3.8%) had the highest IV values (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The supply of tropical wood in Brazil from the Amazon has historically generated enormous economic revenue, but generally has not been sustainably regulated to guarantee maintenance of the forest structure and associated environmental services such as forest carbon stock, maintenance of the hydrological cycle and the genetic biodiversity of the flora (GIMENEZ et al, 2015;CRIVELLI et al , 2017;GAUI et al, 2019). In the context of timber extraction in the state of Roraima, there was a large amount of forest exploitation from 2011 to 2016, a result of deforestation licences (DL) issued by the State Foundation for the Environment and Water Resources of Roraima (FEMARH) in relation to plans for sustainable forest management (PSFM) (CONDÉ et al , 2019), revealing how Roraima public policies aimed at promoting sustainable multi-use forest management, which makes it possible to exploit timber and non-timber products in harmony with nature and the Earth's climate balance, are still in the early stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in forest fires in the Amazon in recent decades is strongly related to the drought-fire interaction, due to the high flammability of dry vegetation in the El Niño years, associated with the indiscriminate use of fire by humans. The increase in selective logging in Amazonia [7], to the detriment of the fall in deforestation rates (2004 to 2012) [3,44], has led to sawmills receiving an alternative constant supply of unauthorized timber [23][24][25]45]. This has been possible, because it is virtually invisible to low spatial resolution sensors (MODIS, Landsat, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The altitude of the region is higher than 65 meters, favoring the occurrence of some of the most exploited timber species in Roraima, such as "maçaranduba"-Manilkara huberi (Ducke) A. Chev. and "angelim-ferro"-Dinizia excelsa Ducke [8,27,33,45]. Estimates of the mean tree density per hectare and the mean forest carbon stock per hectare from this forest inventory (FI) should be restricted to transitional ecosystems or ecotones (forest areas: LOt, between Ld/Ds) only, and should not be applied to campinarana ecosystems (non-forested areas: Lg, Lb, La) on the whole of Flona Anauá.…”
Section: Discussionmentioning
confidence: 99%